2014
DOI: 10.1590/1983-1447.2014.03.42068
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and management of chemotherapy-induced nausea and vomiting in women with breast cancer

Abstract: The objective of this study was to analyze the incidence of chemotherapy-induced nausea and vomiting in women with breast cancer and identify strategies used by them to control these signs and symptoms. Data for this cross-sectional study were collected through interviews during the last cycle of chemotherapy, between August 2011 and March 2012, in a university hospital in the State of São Paulo. The sample consisted of 22 women between the ages of 31 and 70, of whom 77.3% reported nausea and 50% vomiting duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 14 publications
1
9
0
5
Order By: Relevance
“…This indicates that anti-emetics are still not enough in controlling CINV symptoms. This high prevalence also appears in previous studies, which found that nearly 70-80% reported having CINV [ 10 , 19 ]. Also, the finding in this study that there is a higher incidence of CINV during the delayed period than the acute period supports previous literature [ 19 , 20 ].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…This indicates that anti-emetics are still not enough in controlling CINV symptoms. This high prevalence also appears in previous studies, which found that nearly 70-80% reported having CINV [ 10 , 19 ]. Also, the finding in this study that there is a higher incidence of CINV during the delayed period than the acute period supports previous literature [ 19 , 20 ].…”
Section: Discussionsupporting
confidence: 85%
“…Despite the latest improvements in anti-emetics drugs administration, CINV is still considered one of the worst side effects of chemotherapy, impairing the patient’s quality of life (QoL), and if left untreated, it can affect more than 90% of patients on HEC, consequently affecting their willingness to continue chemotherapy [ 9 ]. A Portuguese study showed that 77% of female breast cancer patients reported nausea and 50% reported vomiting at least once [ 10 ]. In Jordan, a research that surveyed cancer patients showed that most had nausea (71.4%) and vomiting (57.3%) [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…In a survey, it was found that 94.4% of the women who had nausea and 77.7% of those who suffered from vomiting said they had been instructed to use the prescribed medication, favoring self-care. 12 As for the change in the skin, nails and mucous membranes, the complaint of vaginal dryness is important when it comes to the relationship of the patient and her partner. As in a study, 145 women were questioned about their quality of life, revealing that 50.50% of them have difficulty in their sexual relationship.…”
Section: It's a Process It's An Effect The Chemotherapy Causes In Fmentioning
confidence: 99%
“…1,2 Os tratamentos projetados para salvar ou prolongar a vida das mulheres podem causar impactos psicológicos, sociais e físicos que alteram a qualidade de vida de quem enfrenta a doença. [3][4][5] Apesar de diversos tratamentos disponíveis, o procedimento cirúrgico ainda compõe uma das modalidades terapêuticas mais utilizadas para o câncer de mama. Entretanto, podem ocorrer complicações pós-operatórias que afetam negativamente, a curto e a longo prazo, as atividades de vida diária, o autocuidado, o desempenho profissional e social da mulher.…”
Section: Introductionunclassified